Scientific Integration of Perspectives M. Amin Abdullah (Integrative-Interconnective Approach) - Nisa A-Zahro Jauzaa’; Rustam Ibrahim (al-Afkar, Journal For Islamic Studies, 2025)
The dichotomy between general science and religious science still occurs, claims of truth about certain Islamic thoughts cause scientific development in the Islamic world to become weak. The ideas of Islamic thinkers in Indonesia include M. Amin Abdullah, with scientific spider web theory with an integrative-interconnective approach. This research aims to determine the integrative-interconnective approach to M thinking. Amen Abdullah. The method used is literature, qualitative-descriptive. With integration-interconnection, the idea promoted is the progress of the Islamic study paradigm from normal science (level Islamic Doctrines), to revolutionary science (level Islamic Studies). The theory initiated by Amin Abdullah is “spider webs” UIN integration-interconnection science which illustrates theoanthroposntric-integralistic spider web relationships.